Effects of social anxiety on metaphorical associations between emotional valence and clothing brightness. (December 2018) - Ishikawa, Kenta; Suzuki, Hikaru; Okubo, Matia
Abstract: Background and Objectives: Individuals with social anxiety have various types of deficiencies in emotional processing. Diversity of deficiencies may imply that socially anxious individuals have malfunctions in fundamental parts of emotional processing. Therefore, we hypothesized that social anxiety contributes to deficiencies in building on the metaphorical relationship between emotional experience and brightness. Methods: We conducted a judgment task of valences of faces with manipulated clothing brightness (bright or dark). Results: A congruency effect between the emotional valence and clothing brightness was observed in participants with low social anxiety. However, this pattern was not found in participants with high social anxiety. The results suggested that a deficiency in metaphorical associations leads to maladaptive emotional processing in individuals with social anxiety. Limitations: Our findings cannot be directly generalized to clinical populations. Such populations should be tested in the future studies. Conclusions: We may expand Lakoff and Johnson's (1999) conceptual metaphor theory by showing the relationships between social anxiety and malfunction in metaphorical processing. Malfunctions in metaphorical processing could lead to various types of psychological disorders which have deficiencies in emotional processing. Highlights: Social anxiety may have deficiencies in building on the metaphorical associations. We conducted a judgment task of valences of faces with manipulated clothing brightness. The size of the metaphorical association decreased with the level of social anxiety. Such deficiency may lead to maladaptive emotional processing in social anxiety.